Analisis Pengaruh PBV, EPS, ROA Terhadap Harga Saham Sektor F&B (BEI 2020-2023) - Dewi Mumpuni Alfi Hidayati; Nur Sayidah (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2025)
This study aims to analyze whether there is an effect of PBV, EPS, and ROA on Stock Prices. The method in this study is a quantitative method using secondary data in the form of financial reports collected through documentation techniques, obtained through the IDX website. The population of this study is food and beverage industry sector companies listed on the IDX for the period 2020-2023 using purposive sampling technique obtained a sample of 80. The method of analysis of this research is descriptive analysis method. The results of this study indicate that partially Price to Book Value and Earning Per Share have a significant positive effect on stock prices, while Return On Asset has a significant negative effect on stock prices. But simultaneously, PBV, EPS, and ROA variables have a significant positive effect on stock prices.